Factors Influencing Poor Outcomes in Synthetic Tissue-Engineered Tracheal Replacement. (September 2019) - Pepper, Victoria; Best, Cameron A.; Buckley, Kaila; Schwartz, Cynthia; Onwuka, Ekene; King, Nakesha; White, Audrey; Dharmadhikari, Sayali; Reynolds, Susan D.; Johnson, Jed; Grischkan, Jonathan; Breuer, Christopher K.; et al.
Objectives: Humans receiving tissue-engineered tracheal grafts have experienced poor outcomes ultimately resulting in death or the need for graft explantation. We assessed the performance of the synthetic scaffolds used in humans with an ovine model of orthotopic tracheal replacement, applying standard postsurgical surveillance and interventions to define the factors that contributed to the complications seen at the bedside. Study Design: Large animal model. Setting: Pediatric academic research institute. Subjects and Methods: Human scaffolds were manufactured with an electrospun blend of polyethylene terephthalate and polyurethane reinforced with polycarbonate rings. They were seeded with autologous bone marrow–derived mononuclear cells and implanted in sheep. Animals were evaluated with routine bronchoscopy and fluoroscopy. Endoscopic dilation and stenting were performed to manage graft stenosis for up to a 4-month time point. Grafts and adjacent native airway were sectioned and evaluated with histology and immunohistochemistry. Results: All animals had signs of graft stenosis. Three of 5 animals (60%) designated for long-term surveillance survived until the 4-month time point. Graft dilation and stent placement resolved respiratory symptoms and prolonged survival. Necropsy demonstrated evidence of infection and graft encapsulation. Granulation tissue with signs of neovascularization was seen at the anastomoses, but epithelialization was never observed. Acute and chronic inflammation of the native airway epithelium was observed at all time points. Architectural changes of the scaffold included posterior wall infolding and scaffold delamination. Conclusions: In our ovine model, clinically applied synthetic tissue-engineered tracheas demonstrated infectious, inflammatory, and mechanical failures with a lack of epithelialization and neovascularization.